The Development of Trust and Mutual Understanding in Social Relations as a Component of the Social Work Education Contents - Hayduk, Nina (Вісник Черкаського національного університету імені Богдана Хмельницького. Серія: "Педагогічні науки", 2016)
The article investigates the issue of training future social workers to apply mediation, an approach of Alternative Dispute Resolution (ADR), as exemplified by the Lviv Polytechnic National University experiences in this area. Based on the adaptation of the USA and Canada experiences in mediation with due regard to Ukrainian peculiarities the model of teaching social work students to apply mediation is defined and incorporated into the contents of teaching. The course outlines are developed based on the identified mediation skills. An emphasis is placed on the transformative concept of mediation highlighting a constructive dialogue, strengthening relations based on trust and mutual understanding, and achieving positive change in people and their problem solution ways. The pedagogical factors and their impact on the development of professional competences of social workers in mediation are identified. The effectiveness of the developed Ukrainian program is proved on the basis of the pedagogical experiment, which illustrates the readiness of future social workers to apply mediation for the purpose of reaching agreement in conflict resolution, and avoiding confrontation and promoting the development of trust and mutual understanding in social relations.